Jarmark Dominikański Gdańsk 3-18 sierpnia 1974 r. - Baliszewska-Walicka, Aleksandra (1939- ).; Walicki, Zdzisław (1940-2008). (Gdańsk : WAG Gdańsk, 1974)
Plakat.
Nazwisko autorów na lewej krawędzi.
Keywords: Jarmarki -- Polska -- Gdańsk -- 1945-1990.